“Aos meninos do Brasil”: a estética literária para crianças em Histórias da Velha Totônia (1936), de José Lins do Rego - Ebizero, Amanda Topic [UNIFESP] (2020)
In this Master’s dissertation presentes research results connected to the Integrated Research Project “Brazilian children's and young literature revisited: themes, forms, purposes and historical, cultural and esthetic value of literary production in the 19th and 20th centuries”, coordinated by Professor Dr. Fernando Rodrigues de Oliveira. In order to contribute to the production of a history of children's and young literature and to understand how the literary esthetic for children are configured in books produced throughout the twentieth century in Brazil, is used as a corpus of analysis the book Histórias da velha Totônia, by José Lins do Rego (1901-1957), published by José Olympio Editora (RJ) in 1936. Through the historical approach, specifically Cultural History, with a focus on documentary and bibliographical research, the work was developed through procedures for locating, retrieving, assembling, selecting, ordering and analyzing documentary sources, using the concept of “textual configuration”. This analysis made it possible to conclude that José Lins do Rego, in writing Histórias da velha Totônia, in dialogue with the child and school models in force at the time, presented a book in line with the ideal of schooling centered on the assumption of the construction of the future of nation, based on the republican perspective of the time, moreover, did not neglect the elaborate work of construction of the text, which gives it a literary esthetic value to be recognized. In this sense, without completely disconnecting from the children's literature model of the early 20th century, whose main purpose was centered on the objective of school instruction, José Lins do Rego presented in Histórias da velha Totônia characteristics that make it possible to rethink aspects of the history of literature brazilian children's, in order to understand the relationship between instruction/esthetics in children's literature books of the early 20th century.